2018
DOI: 10.15561/20755279.2018.0507
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Exhaustive Aerobic, Anaerobic and Resistance Exercise on Serotonin, Beta-endorphin and BDNF in Students

Abstract: Background and Study Aim: Sport exercises play a major role in many hormonal factors which related to happiness in human. Therefore, the short-term effects of three anaerobic, aerobic and resistance exercises on (BDNF) and hormones related to happiness such as serotonin and beta-endorphin has been studied in young men in this research. Materials and Methods: Thirty-two students (19 to 25 years old) who did not have regular physical activity were randomly divided into four groups, after the subjects were eaten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…These results indicated that the activation of 5-HT neurons was closely related to the intensity and duration of exercise and that the low-intensity exercise seemed to be more effective in activating 5-HT neurons. Similar results were found in the human experiment, where one session of aerobic exercise rather than anaerobic exercise led to a significant effect on serotonin release (Sharifi et al, 2018 ). In this study, we specifically designed the exercise protocol which contained a flexible moderate intensity protocol, and whole-cell patch clamp recording was performed 24 h following the last training, which allowed 5-HT neurons to adapt to their resting state.…”
Section: Discussionsupporting
confidence: 83%
“…These results indicated that the activation of 5-HT neurons was closely related to the intensity and duration of exercise and that the low-intensity exercise seemed to be more effective in activating 5-HT neurons. Similar results were found in the human experiment, where one session of aerobic exercise rather than anaerobic exercise led to a significant effect on serotonin release (Sharifi et al, 2018 ). In this study, we specifically designed the exercise protocol which contained a flexible moderate intensity protocol, and whole-cell patch clamp recording was performed 24 h following the last training, which allowed 5-HT neurons to adapt to their resting state.…”
Section: Discussionsupporting
confidence: 83%
“…In consonance with previous research (36,42) the current study demonstrated an elevation of circulating βEP concentration following HI-AE. In the peripheral nervous system, beta-endorphin produces analgesia by binding to opioid receptors and inhibiting the release of substance P, a key protein involved in the transmission of pain (46,55).…”
Section: Discussionsupporting
confidence: 93%
“…Regular engagement in physical activity is associated with the levels of life stress of participants [60,61]. This reduction in life stress occurs due to the release of endorphins which have a natural calming effect on the nervous system and reduce cortisol levels [62]. Further, engagement in physical activity has been shown to be an efficacious alternative strategy for overcoming or avoiding feelings of frustration, improving the mood state and reducing levels of anxiety and life stress [63].…”
Section: Discussionmentioning
confidence: 99%